Sharia Compliance In Digital Finance Platforms: Evidence From Women MSME Entrepreneurs - Natasya Nabila Putri; Muhammad Fauzi; Alek Wissalam Bustami (IQTISHOD: Jurnal Pemikiran dan Hukum Ekonomi Syariah, 2026)
This study examines the use of digital Islamic financial platforms among women-owned micro, small, and medium enterprises (MSMEs) in Indonesia, a segment that continues to grow but remains underrepresented in the digital finance ecosystem. The main problem addressed in this research is the limited understanding and varied experiences of women entrepreneurs in accessing and utilizing Sharia based digital financial services, despite increasing national digitalization efforts. Using a qualitative approach, this study employs in depth interviews with selected women MSME owners to explore their conceptual understanding of Islamic digital finance, their practical experiences in using available platforms, and the opportunities and challenges they encounter in the process. The findings show that, while most participants understand general Sharia principles such as the prohibition of riba and the importance of transparent contracts, their comprehension of digital Islamic finance remains partial. The study also reveals that digital platforms offer greater convenience, efficiency, and access to capital, yet challenges persist, including limited digital literacy, inconsistent platform usability, and concerns about Sharia compliance.